2020
DOI: 10.4103/jmau.jmau_61_20
|View full text |Cite
|
Sign up to set email alerts
|

Advantages of Kahoot! Game.based Formative Assessments along with Methods of Its Use and Application during the COVID-19 Pandemic in Various Live Learning Sessions

Abstract: Background: Technology has played important roles in education, thus the application of online Kahoot! Game-based technology as a learning tool particularly in formative assessments might improve learning and achieve promising education. It can be applied live, either face to face or virtual in distance learning as during the current situation of COVID-19 pandemic that resulted in total shift toward online learning. Methodology: Kahoot! Game-based histology and cell bio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
40
0
13

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(55 citation statements)
references
References 32 publications
2
40
0
13
Order By: Relevance
“…The use of this method has produced positive results in the COVID-19 context ( Nieto-Escamez and Roldán-Tapia, 2021 ; Rincon-Flores and Santos-Guevara, 2021 ). Moreover, gamification has been used in different subjects, such as business ( Pakinee and Puritat, 2021 ), computer sciences ( Liénardy and Donnet, 2020 ), and chemistry learning ( da Silva Júnior et al, 2020a , b ), as well as biological sciences courses, such as biology ( Kalleny, 2020 ; Lobet et al, 2021 ), microbiology ( Dustman et al, 2021 ), physiology ( Moro et al, 2020 ; Hennekes et al, 2021 ; Herkes et al, 2021 ; Kane et al, 2022 ), and medical and nursing education ( Gentry et al, 2019 ; Malicki et al, 2020 ; O’Connell et al, 2020 ; van Gaalen et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…The use of this method has produced positive results in the COVID-19 context ( Nieto-Escamez and Roldán-Tapia, 2021 ; Rincon-Flores and Santos-Guevara, 2021 ). Moreover, gamification has been used in different subjects, such as business ( Pakinee and Puritat, 2021 ), computer sciences ( Liénardy and Donnet, 2020 ), and chemistry learning ( da Silva Júnior et al, 2020a , b ), as well as biological sciences courses, such as biology ( Kalleny, 2020 ; Lobet et al, 2021 ), microbiology ( Dustman et al, 2021 ), physiology ( Moro et al, 2020 ; Hennekes et al, 2021 ; Herkes et al, 2021 ; Kane et al, 2022 ), and medical and nursing education ( Gentry et al, 2019 ; Malicki et al, 2020 ; O’Connell et al, 2020 ; van Gaalen et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…Overall content coverage (3.97). The results show a lower score for practical skills since practical usually need skills that required f2f 1 Kalleny (2020) [ 73 ] OL; UG medical students from the Faculty of Medicine Ain Shams University Online questionnaire Traditional learning ( N = 136) Cross-sectional study Students were satisfied with Kahoot. The overall rating score is 4.65 out of 5 1 Khalaf et al (2020) [ 74 ] OL; UG dental students at University of Sharjah Online questionnaire Traditional learning ( N = 65) Cross-sectional study Students were very satisfied with the online exam.…”
Section: Resultsmentioning
confidence: 99%
“…A cross-continent comparison of the level of satisfaction was also conducted. From the 13 studies that reported higher satisfaction with the use of online learning approach, six were from Asia [ 26 , 51 , 56 , 62 , 74 , 75 ], five were from Europe [ 32 , 41 , 47 , 66 ], one from America [ 77 ], and one from Africa [ 73 ]. Meanwhile, five studies from Asia [ 43 , 58 , 61 , 65 , 68 ] and one study from Africa [ 35 ] revealed that students were not satisfied with online learning.…”
Section: Resultsmentioning
confidence: 99%
“…The embedded visual and audio elements in Kahoot! game will be very helpful and its good features help in promoting engagement, motivation, and learning among middle-aged (Kalleny, 2020 ). Besides that, Kahoot!…”
Section: Literature Reviewmentioning
confidence: 99%